FRIB cryogenic control system. Issue 1 (March 2020) - Joseph, N; Vargas, G; Stanley, S; Dudley, C; Thrush, M; Strong, H; Knudsen, P; Ganni, V; Casagrande, F
Abstract: The cryogenic system at the Facility for Rare Isotope Beams (FRIB) supports loads for 2 K refrigeration, 4.5 K refrigeration and liquefaction, and a 35-55 K thermal shield for the linear accelerator consisting of 46 cryomodules, 4 superconducting dipoles and 14 superconducting magnets for the experimental system. The controls system for cryogenics was designed, installed, and commissioned with the goal of high availability, ease of maintenance, and simplicity of operation. The personnel protection system (PPS) is a separate system which monitors for oxygen deficiency hazards (ODH) throughout the cryo-plant and around the cryogenic loads. The system consists of Allen-Bradley programmable logic controllers (PLCs) with local human machine interfaces (HMIs) along with the Experimental Physics and Industrial Controls System (EPICS) for normal operations and data acquisition. Two separate networks are utilized in the cryogenic facility. One is a network cluster that houses EPICS. It is designed with high redundancy and is completely separate from the network used for the rest of the particle accelerator. The second network only includes PLCs and HMIs for faster data transfer between PLCs, increased flexibility for changing operating conditions, and complete system operation in the case of an EPICS network failure. This paper reports on the design choices selected and experiences in integrating and commissioning the FRIB cryogenic control system.